Ovary activation does not correlate with pollen and nectar foraging specialization in the bumblebee Bombus impatiens - Meagan A. Simons (PeerJ, 2018)
Social insect foragers may specialize on certain resource types. Specialization on pollen or nectar among honeybee foragers is hypothesized to result from associations between reproductive physiology and sensory tuning that evolved in ancestral solitary bees (the Reproductive Ground-Plan Hypothesis; RGPH). However, the two non-honeybee species studied showed no association between specialization and ovary activation. Here we investigate the bumblebee B. impatiens because it has the most extensively studied pollen/nectar specialization of any bumblebee. We show that ovary size does not differ between pollen specialist, nectar specialist, and generalist foragers, contrary to the predictions of the RGPH. However, we also found mixed support for the second prediction of the RGPH, that sensory sensitivity, measured through proboscis extension response (PER), is greater among pollen foragers. We also found a correlation between foraging activity and ovary size, and foraging activity and relative nectar preference, but no correlation between ovary size and nectar preference. In one colony non-foragers had larger ovaries than foragers, supporting the reproductive conflict and work hypothesis, but in the other colony they did not.